Intimate partner violence and COVID-19 in rural, remote, and northern Canada: relationship, vulnerability and risk - Moffitt, Pertice (Journal of family violence, 2022)
In rural, remote, and northern parts of Canada, the pre-existing vulnerability and risk for intimate partner violence has been exacerbated by COVID-19. The purpose of this commentary is to identify the unique impact of COVID-19 on intimate partner violence both in terms of the bearing on those experiencing abuse and on the service sector in rural, remote and northern communities where the rates of intimate partner violence and intimate partner femicide pre-pandemic are higher than in larger cities. The recommendations offered in this paper include enhanced safety planning, alternate housing for victims fleeing violence, and suggestions for service providers. We also offer ways to move forward with further research in the COVID-19 era.